Nanofiber hemostatic bandage and application thereof
Through the multi-layer structure designed nanofiber hemostasis bandage, combined with nano zinc oxide, microencapsulated biochemical hemostasis zone and inflatable polymer materials, the shortcomings of existing hemostasis materials in antibacteriality, functional synergy and hemostasis efficiency are solved, and rapid and effective hemostasis and wound care are achieved.
Patent Information
- Application Number
- CN202411747011.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
AI Technical Summary
Existing hemostatic materials have shortcomings in antibacteriality, functional synergy and hemostatic efficiency, which is difficult to meet complex clinical needs.
The nanofiber hemostasis bandage designed with a multi-layer structure, including a nanofiber material layer embedded in nanozinc oxide, a microencapsulated biochemical hemostasis area and a blood stop response layer of inflatable polymer materials, to achieve the synergistic effect of physical hemostasis, chemical hemostasis and swelling hemostasis.
It achieves rapid and effective hemostasis, enhances antibacterial properties, maintains the breathability and water resistance of the wound, and significantly improves the hemostasis efficiency and applicability.
Smart Images

Figure CN119564909A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of medical equipment, in particular to a nanofiber hemostatic bandage and application thereof. Background Art
[0002] Hemostasis technology is a research focus in the field of medicine and emergency rescue. In particular, efficient and rapid hemostasis solutions are particularly important in scenarios such as trauma, surgery, and battlefield first aid. Traditional hemostatic products mainly rely on single physical blocking or chemical coagulation methods, but in the face of severe trauma or heavy bleeding, they are often difficult to meet clinical needs due to slow hemostasis or limited functions. At the same time, traditional hemostatic materials have weak antibacterial properties, and wounds are prone to infection, further increasing the complexity of postoperative care and rehabilitation.
[0003] In recent years, nanomaterials have shown great potential in the field of hemostasis due to their unique physical and chemical properties. In particular, nano zinc oxide has gradually become a research hotspot for hemostatic materials due to its excellent antibacterial properties and biocompatibility. However, there are still technical difficulties in combining nano zinc oxide with traditional hemostatic materials and maintaining the material's air permeability and resistance to liquid penetration while meeting hemostasis requirements. In addition, how to achieve the synergistic effect of physical hemostasis, chemical hemostasis, and swelling hemostasis through multi-layer structure design to further improve hemostasis efficiency and applicability has also been a key research direction.
[0004] Most of the hemostatic products on the market are currently designed with a single-layer structure, such as ordinary hemostatic gauze or gelatin sponge, which rely on absorbing blood to form initial coagulation, but have limited effects in scenarios such as arterial bleeding. Although some functional hemostatic products improve hemostatic performance by adding biological hemostatic factors or expansive materials, they lack targeted design, insufficient material stability and functional synergy, and are difficult to meet complex clinical needs. Therefore, there is an urgent need for a multifunctional hemostatic material that can integrate antibacterial, breathable, chemical hemostatic and expansive hemostatic functions to improve the hemostatic effect in emergency and surgical care.
[0005] Aiming at the deficiencies of existing hemostatic materials in terms of antibacterial property, functional synergy and hemostatic efficiency, the present invention proposes a nanofiber hemostatic bandage. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a nanofiber hemostatic bandage and its application, which solves the problems of the existing hemostatic materials in terms of antibacterial properties, air permeability, water impermeability and hemostatic efficiency.
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions: A nanofiber hemostatic bandage includes the following structural layers, from outside to inside:
[0008] A protective sheet, which is used to cover the surface of the hemostatic bandage before use to protect it from contamination;
[0009] a nanofiber material layer, which serves as a base layer of the hemostatic bandage;
[0010] The biochemical hemostasis zone is arranged in the middle of the surface of the nanofiber material layer and is used to release coagulation factors after encountering blood to accelerate coagulation;
[0011] An adhesive layer, which is located around the nanofiber material layer and is used to fix the hemostatic bandage so that it fits on the skin;
[0012] The blood stop response layer is located below the biochemical hemostasis zone and is used to rapidly swell to form a physical barrier and release coagulation factors after encountering blood.
[0013] Preferably, the nanofiber material layer comprises components: polyethylene terephthalate, polyvinylidene fluoride substrate and 20nm nano zinc oxide;
[0014] The polyethylene terephthalate and polyvinylidene fluoride materials account for 85-95wt% of the nanofiber material layer, and the nano zinc oxide accounts for 5-15wt% of the nanofiber material layer.
[0015] Preferably, the preparation method of the nanofiber material layer is as follows:
[0016] S1.1, preparing an electrospinning solution: polyethylene terephthalate and polyvinylidene fluoride are mixed and dissolved in a mixed solvent of dimethylformamide and tetrahydrofuran at a total mass of 85-95wt%, and stirred to form a uniform solution by heating to 60-70°C; nano zinc oxide with a particle size of 20nm accounting for 5-15wt% of the solution mass is added to the solution, and ultrasonic dispersion is used for 15-20min and then continued to stir to form a uniform electrospinning solution;
[0017] S1.2, electrospinning: electrospinning the electrospinning solution at a voltage of 15-25 kV, a flow rate of 0.5-1.5 mL / h, and a distance of 10-20 cm between the needle and the receiving plate, and stretching to form a nanofiber membrane with a pore size of 0.2-0.5 μm, wherein the nano zinc oxide is uniformly embedded in the fiber structure, and the content of the nano zinc oxide in each square meter of the fiber membrane is 1-2 g;
[0018] S1.3, drying, heat treatment and molding: the nanofiber membrane prepared by electrospinning is left to dry at room temperature for 2-4 hours to remove the residual solvent, and then heat treated at 60-80°C for 2-4 hours, and finally cut into the required size to prepare the nanofiber material layer.
[0019] Preferably, the biochemical hemostatic zone comprises components: biological hemostatic factors, hydrophilic nanofibers and microcapsule wrapping materials;
[0020] The biological hemostatic factor accounts for 40-60wt% of the biochemical hemostatic area. The biological hemostatic factor is a coagulation protein and a hemostatic enzyme. The coagulation protein is fibrinogen, and the hemostatic enzyme is snake venom thrombin. The hydrophilic nanofiber accounts for 20-40wt% of the biochemical hemostatic area. The microcapsule wrapping material is optionally one of gelatin, chitosan or polylactic acid-glycolic acid, which accounts for 10-20wt% of the biochemical hemostatic area.
[0021] Preferably, the preparation method of the biochemical hemostatic zone is as follows:
[0022] S2.1. Dissolving the microcapsule encapsulation material: dissolving gelatin, chitosan or polylactic acid-glycolic acid in deionized water or ethanol at a ratio of 10-20 wt % at a dissolving temperature of 20-40° C., stirring for 30-60 min until completely dissolved to form a uniform solution;
[0023] S2.2, microencapsulation of biological hemostatic factors: slowly add 40-60wt% biological hemostatic factor solution into the encapsulating material solution at a rate of 0.5-2mL / min, stir at 300-800rpm at 20-30°C to form an emulsion, and solidify the encapsulating material by evaporating the solvent or heating to obtain microencapsulated coagulation protein and hemostatic enzyme particles with a particle size of 100-500μm;
[0024] S2.3, preparation of hydrophilic nanofiber support material: dissolve polyethylene glycol or polyvinyl alcohol in deionized water or ethanol at a ratio of 8-15wt%, heat to 60-70°C and stir for 1-2h to form a uniform spinning solution, spin it into a hydrophilic nanofiber membrane by electrospinning technology at a voltage of 10-20kV, a flow rate of 0.2-1.0mL / h and a spinning distance of 10-15cm, and cut the spun nanofiber membrane into a size that meets the specifications of the biochemical hemostasis area, accounting for 20-40wt% of the biochemical hemostasis area;
[0025] S2.4, microcapsule fixation: the microencapsulated biological hemostatic factor is evenly sprayed on the surface of the hydrophilic nanofiber membrane at a concentration of 5-10wt% and a spraying rate of 0.5-2mL / min. It is naturally dried at room temperature so that the microcapsule particles are firmly attached to the surface of the hydrophilic nanofiber membrane to form a biochemical hemostatic zone.
[0026] Preferably, the blood stop response layer comprises components: expandable polymer material, microencapsulated coagulation factor and fixed adhesive;
[0027] The expandable polymer material is optionally one of sodium polyacrylate or polyurethane, which accounts for 60-80wt% of the blood stop response layer; the microencapsulated coagulation factors include coagulation proteins and hemostatic enzymes, which account for 15-30wt% of the blood stop response layer; the fixing adhesive is optionally one of sodium alginate or gelatin, which accounts for 5-10wt% of the blood stop response layer.
[0028] Preferably, the preparation method of the blood stop response layer is as follows:
[0029] S3.1. Preparation of expandable polymer material membrane:
[0030] Dissolve or disperse the expandable polymer material in deionized water at 60-80 wt% of the mass of the solution, stir evenly for 30-60 min to form an expandable solution, use a coating device to evenly coat the solution on the surface of the substrate, control the coating thickness to 100-300 μm, and dry at room temperature for 2-4 h to form an expandable polymer material film;
[0031] S3.2. Microencapsulation of biological hemostatic factors:
[0032] Mix the coagulation protein and hemostatic enzyme in proportion, accounting for 40-60wt% of the mass of the biological hemostatic factor solution, add it into 40-60wt% deionized water and stir evenly, dissolve the wrapping material in deionized water or ethanol at a ratio of 10-20wt%, stir for 30-60min, and the dissolution temperature is 20-40℃;
[0033] Slowly adding the biological hemostatic factor solution to the encapsulating material solution at a rate of 0.5-2 mL / min, stirring at 300-800 rpm at 20-30° C. to form an emulsion, and solidifying by volatilizing the solvent or heating to 30-50° C. to form microcapsule particles with a particle size of 100-500 μm;
[0034] S3.3, Microcapsule fixation and molding:
[0035] The microencapsulated biological hemostatic factor is uniformly sprayed on the surface of the expandable polymer material film at a concentration of 5-10wt% and a spraying rate of 0.5-2mL / min;
[0036] S3.4, prepare the fixing adhesive solution: dissolve 5-10wt% of sodium alginate or gelatin in 90-95wt% deionized water or ethanol, heat to 40-50°C and stir evenly;
[0037] S3.5, spray the fixing adhesive solution evenly on the surface of the microcapsule particles at a spraying rate of 0.5-1.5 mL / min;
[0038] S3.6. Allow the sprayed film to dry naturally at room temperature for 1-3 hours to form a blood-stopping response layer.
[0039] The application of the nanofiber hemostatic bandage in the following scenarios:
[0040] Used for emergency trauma hemostasis, including open wounds and deep wounds;
[0041] For bleeding control during surgery;
[0042] Used for rapid hemostasis in battlefield emergency situations;
[0043] Used for rapid hemostasis of arterial bleeding, capillary bleeding and other heavy bleeding wounds;
[0044] Used for local hemostasis operation and postoperative hemostasis care in medical institutions;
[0045] Used for hemostatic protection of accidental wounds in industrial or domestic environments.
[0046] The present invention provides a nanofiber hemostatic bandage and its application, which has the following beneficial effects:
[0047] 1. The present invention realizes the comprehensive effects of physical hemostasis, chemical hemostasis and swelling hemostasis through multi-layer structural design. The nanofiber material layer provides excellent base support and antibacterial function. Nano zinc oxide with a particle size of 20nm is evenly embedded in the fiber through the electrospinning process, which effectively inhibits bacterial reproduction. The pore size of the fiber membrane is 0.2-0.5μm, which can block bacteria and liquids and allow air to pass through, so that the wound maintains a dry and breathable environment. The breathable and impermeable characteristics not only reduce the risk of infection, but also provide more favorable conditions for wound healing. The excellent performance of the base layer provides a solid foundation for the overall performance of the hemostatic bandage.
[0048] 2. The biochemical hemostatic zone of the present invention is an important part for realizing the chemical hemostatic function. This zone ensures the stability and controllable release of coagulation factors by microencapsulating biological hemostatic factors such as fibrinogen and snake venom thrombin. The design of the microencapsulated particles enables them to gradually release coagulation factors when encountering blood and quickly initiate the coagulation reaction. The hydrophilic nanofiber support material quickly absorbs blood and guides it to the coagulation factor action area through its good liquid absorption performance, thereby improving the coagulation efficiency. This design not only improves the hemostatic efficiency, but also avoids the possibility of affecting the function due to excessive blood accumulation.
[0049] 3. The blood-stopping response layer of the present invention realizes rapid expansion and barrier protection functions through expandable polymer materials. After contacting blood, this layer of material can quickly absorb water and expand to form a strong physical barrier, effectively preventing blood outflow. At the same time, the hemostatic function is further enhanced by the release of microencapsulated coagulation factors. The dual effects of expansion hemostasis and barrier protection make this structural layer particularly outstanding in treating large bleeding wounds such as arterial bleeding, which significantly improves the emergency hemostasis effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is a schematic diagram of the structure of the nanofiber hemostatic bandage of the present invention;
[0051] Figure 2 is a flow chart for preparing the nanofiber material layer of the present invention;
[0052] Figure 3 The present invention is a flow chart for preparing the biochemical hemostatic zone;
[0053] Figure 4 The figure is a flow chart for preparing the blood stop response layer of the present invention;
[0054] Figure 5 This is a data chart of the in vitro coagulation activity assay results of the present invention;
[0055] Figure 6 The data chart of the determination result of the in vitro coagulation time of the present invention;
[0056] Figure 7 This is a data chart of the plasma recalcification time measurement results of the present invention.
[0057] Among them, 1. Nanofiber material layer; 2. Biochemical hemostasis area; 3. Adhesive layer; 4. Blood hemostasis response layer; 5. Protective sheet. DETAILED DESCRIPTION
[0058] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0059] Please refer to the attached Figure 1 The embodiment of the present invention provides a nanofiber hemostatic bandage, comprising the following structural layers, from outside to inside:
[0060] A protective sheet 5, which is used to cover the surface of the hemostatic bandage before use to protect it from contamination;
[0061] A nanofiber material layer 1, which serves as a base layer of the hemostatic bandage;
[0062] The biochemical hemostasis zone 2 is arranged in the middle of the surface of the nanofiber material layer 1 and is used to release coagulation factors after encountering blood to accelerate coagulation;
[0063] An adhesive layer 3, which is located around the nanofiber material layer 1 and is used to fix the hemostatic bandage so that it fits on the skin;
[0064] The blood stop response layer 4 is located below the biochemical hemostasis zone 2 and is used to expand rapidly to form a physical barrier and release coagulation factors after encountering blood.
[0065] Specifically, the protective sheet is made of sterile medical non-woven fabric or waterproof film material, which covers the surface of the hemostatic bandage. Its main function is to prevent contamination before use. At the same time, it has waterproof properties, effectively blocks external liquids and dust, and provides cleanliness guarantee for subsequent use.
[0066] The nanofiber material layer 1 is used as the base layer of the hemostatic bandage. It uses polyethylene terephthalate (PET) or polyvinylidene fluoride (PVDF) as the base material, and is embedded with nano zinc oxide with a particle size of 20nm through an electrospinning process. Its pore size is precisely controlled at 0.2-0.5μm, which can not only block bacteria and liquids, but also allow gas to pass through to maintain the breathability of the wound. This breathable and impermeable property effectively reduces the risk of wound infection and creates a more ideal environment for wound healing. At the same time, nano zinc oxide is evenly distributed in the fiber structure, showing excellent antibacterial ability, further enhancing the practicality of the material.
[0067] The biochemical hemostasis area 2 is set in the middle of the nanofiber material layer 1, and its design core is to achieve chemical hemostasis function. By microencapsulating biological hemostatic factors such as fibrinogen and snake venom thrombin and fixing them on the hydrophilic nanofiber membrane, this area can quickly start the coagulation reaction when encountering blood. The hydrophilic nanofiber membrane quickly absorbs blood through its excellent liquid absorption performance and guides it to the action area of the microcapsule particles, ensuring the accuracy and efficiency of the release of hemostatic factors.
[0068] The adhesive layer 3 surrounds the nanofiber material layer 1 and is used to firmly fix the hemostatic bandage on the skin surface. It uses a medical-grade non-toxic adhesive to ensure the stability of adhesion without irritating the skin. The design of the adhesive layer 3 is precise to avoid the possibility of interfering with the functions of the biochemical hemostatic zone 2 and the blood stop response layer 4, maintaining the consistency of the overall performance of the hemostatic bandage.
[0069] The blood stop response layer 4 is located below the biochemical hemostasis zone 2, and realizes the dual functions of expansion hemostasis and physical barrier through the combination of expandable polymer material and microencapsulated coagulation factor. When in contact with blood, the expandable polymer material quickly absorbs water and swells, forming an effective physical barrier to prevent blood from flowing out. At the same time, the microcapsule particles gradually release coagulation factors, which complement the expansion effect and greatly shorten the hemostasis time. The design of this layer makes it particularly effective in treating large bleeding wounds such as arterial bleeding, and improves the ability of emergency hemostasis.
[0070] Through the organic combination of the above-mentioned multi-layer structure, the present invention realizes multiple functions of rapid hemostasis, antibacterial, waterproof and breathable, and firm fixation, providing an ideal solution for various scenarios such as emergency trauma, surgical operations, and battlefield first aid.
[0071] The nanofiber material layer 1 includes components: polyethylene terephthalate, polyvinylidene fluoride substrate and 20nm nano zinc oxide;
[0072] The polyethylene terephthalate and polyvinylidene fluoride materials account for 85-95wt% of the nanofiber material layer 1 , and the nano zinc oxide accounts for 5-15wt% of the nanofiber material layer 1 .
[0073] Please refer to the attached Figure 2 , the preparation method of the nanofiber material layer 1 is as follows:
[0074] S1.1, preparing an electrospinning solution: polyethylene terephthalate and polyvinylidene fluoride are mixed and dissolved in a mixed solvent of dimethylformamide and tetrahydrofuran at a total mass of 85-95wt%, and stirred to form a uniform solution by heating to 60-70°C; nano zinc oxide with a particle size of 20nm accounting for 5-15wt% of the solution mass is added to the solution, and ultrasonic dispersion is used for 15-20min and then continued to stir to form a uniform electrospinning solution;
[0075] S1.2, electrospinning: electrospinning the electrospinning solution at a voltage of 15-25 kV, a flow rate of 0.5-1.5 mL / h, and a distance of 10-20 cm between the needle and the receiving plate, and stretching to form a nanofiber membrane with a pore size of 0.2-0.5 μm, wherein the nano zinc oxide is uniformly embedded in the fiber structure, and the content of the nano zinc oxide in each square meter of the fiber membrane is 1-2 g;
[0076] S1.3, drying, heat treatment and molding: the nanofiber membrane prepared by electrospinning is left to dry at room temperature for 2-4 hours to remove the residual solvent, and then heat treated at 60-80°C for 2-4 hours, and finally cut into the required size to prepare the nanofiber material layer 1.
[0077] The biochemical hemostasis zone 2 includes components: biological hemostatic factors, hydrophilic nanofibers and microcapsule packaging materials;
[0078] The biological hemostatic factors account for 40-60wt% of the biochemical hemostatic zone 2. The biological hemostatic factors are coagulation proteins and hemostatic enzymes. The coagulation protein is fibrinogen, and the hemostatic enzyme is snake venom thrombin. The hydrophilic nanofibers account for 20-40wt% of the biochemical hemostatic zone 2. The microcapsule encapsulation material is optionally one of gelatin, chitosan or polylactic acid-glycolic acid, which accounts for 10-20wt% of the biochemical hemostatic zone 2.
[0079] Please refer to the attached Figure 3 , the preparation method of biochemical hemostasis zone 2 is as follows:
[0080] S2.1. Dissolving the microcapsule encapsulation material: dissolving gelatin, chitosan or polylactic acid-glycolic acid in deionized water or ethanol at a ratio of 10-20 wt % at a dissolving temperature of 20-40° C., stirring for 30-60 min until completely dissolved to form a uniform solution;
[0081] S2.2, microencapsulation of biological hemostatic factors: slowly add 40-60wt% biological hemostatic factor solution into the encapsulating material solution at a rate of 0.5-2mL / min, stir at 300-800rpm at 20-30°C to form an emulsion, and solidify the encapsulating material by evaporating the solvent or heating to obtain microencapsulated coagulation protein and hemostatic enzyme particles with a particle size of 100-500μm;
[0082] S2.3, preparation of hydrophilic nanofiber support material: dissolve polyethylene glycol or polyvinyl alcohol in deionized water or ethanol at a ratio of 8-15wt%, heat to 60-70°C and stir for 1-2h to form a uniform spinning solution, spin it into a hydrophilic nanofiber membrane by electrospinning technology at a voltage of 10-20kV, a flow rate of 0.2-1.0mL / h and a spinning distance of 10-15cm, cut the spun nanofiber membrane into a size that meets the specifications of the biochemical hemostasis zone, accounting for 20-40wt% of the biochemical hemostasis zone;
[0083] S2.4, microcapsule fixation: the microencapsulated biological hemostatic factor is uniformly sprayed on the surface of the hydrophilic nanofiber membrane at a concentration of 5-10wt% and a spraying rate of 0.5-2mL / min. It is naturally dried at room temperature so that the microcapsule particles are firmly attached to the surface of the hydrophilic nanofiber membrane to form a biochemical hemostatic zone 2.
[0084] The blood stop response layer 4 includes components: expandable polymer material, microencapsulated coagulation factor and fixed adhesive;
[0085] The expandable polymer material is optionally one of sodium polyacrylate or polyurethane, which accounts for 60-80wt% of the blood stop response layer 4, the microencapsulated coagulation factors include coagulation proteins and hemostatic enzymes, which account for 15-30wt% of the blood stop response layer 4, and the fixed adhesive is optionally one of sodium alginate or gelatin, which accounts for 5-10wt% of the blood stop response layer 4.
[0086] Please refer to the attached Figure 4 , the preparation method of the blood stop response layer 4 is as follows:
[0087] S3.1. Preparation of expandable polymer material membrane:
[0088] Dissolve or disperse the expandable polymer material in deionized water at 60-80 wt% of the mass of the solution, stir evenly for 30-60 min to form an expandable solution, use a coating device to evenly coat the solution on the surface of the substrate, control the coating thickness to 100-300 μm, and dry at room temperature for 2-4 h to form an expandable polymer material film;
[0089] S3.2. Microencapsulation of biological hemostatic factors:
[0090] Mix the coagulation protein and hemostatic enzyme in proportion, accounting for 40-60wt% of the mass of the biological hemostatic factor solution, add it into 40-60wt% deionized water and stir evenly, dissolve the wrapping material in deionized water or ethanol at a ratio of 10-20wt%, stir for 30-60min, and the dissolution temperature is 20-40℃;
[0091] Slowly adding the biological hemostatic factor solution to the encapsulating material solution at a rate of 0.5-2 mL / min, stirring at 300-800 rpm at 20-30° C. to form an emulsion, and solidifying by volatilizing the solvent or heating to 30-50° C. to form microcapsule particles with a particle size of 100-500 μm;
[0092] S3.3, Microcapsule fixation and molding:
[0093] The microencapsulated biological hemostatic factor is uniformly sprayed on the surface of the expandable polymer material film at a concentration of 5-10wt% and a spraying rate of 0.5-2mL / min;
[0094] S3.4, prepare the fixing adhesive solution: dissolve 5-10wt% of sodium alginate or gelatin in 90-95wt% deionized water or ethanol, heat to 40-50°C and stir evenly;
[0095] S3.5, spray the fixing adhesive solution evenly on the surface of the microcapsule particles at a spraying rate of 0.5-1.5 mL / min;
[0096] S3.6. Allow the sprayed film to dry naturally at room temperature for 1-3 hours to form a blood-stopping response layer 4.
[0097] Application of nanofiber hemostatic bandage in the following scenarios:
[0098] Used for emergency trauma hemostasis, including open wounds and deep wounds;
[0099] For bleeding control during surgery;
[0100] Used for rapid hemostasis in battlefield emergency situations;
[0101] Used for rapid hemostasis of arterial bleeding, capillary bleeding and other heavy bleeding wounds;
[0102] Used for local hemostasis operation and postoperative hemostasis care in medical institutions;
[0103] Used for hemostatic protection of accidental wounds in industrial or domestic environments.
[0104] Example 1: Basic nanofiber hemostatic bandage
[0105] preparation:
[0106] Nanofiber material layer 1:
[0107] Components: polyethylene terephthalate (90 wt%), nano zinc oxide (10 wt%).
[0108] Preparation: Dissolve in dimethylformamide and tetrahydrofuran (DMF = 1:1), heat to 65°C and stir to dissolve, disperse by ultrasonic for 20 minutes, and then electrospin (voltage 20 kV, flow rate 1 mL / h, spinning distance 15 cm). The fiber pore size is 0.3 μm, and the content of nano zinc oxide in each square meter of fiber membrane is 1.5 g.
[0109] Heat treatment: 70℃, 3 hours.
[0110] Biochemical hemostasis zone 2:
[0111] Components: fibrinogen (50wt%), snake venom thrombin (10wt%), hydrophilic nanofibers (25wt%), and gelatin wrapping material (15wt%).
[0112] Preparation: Gelatin (15 wt%) was dissolved in 30°C water, and coagulation factor solution (fibrinogen and snake venom thrombin) was added to form an emulsion, stirred at 500 rpm, and the particle size was 300 μm. The hydrophilic fiber membrane was prepared from PVA (10 wt%), with a voltage of 15 kV and a pore size of 0.4 μm.
[0113] Blood Stop Response Layer 4:
[0114] Components: sodium polyacrylate (70wt%), microencapsulated coagulation factor (20wt%), sodium alginate (10wt%).
[0115] Preparation: Sodium polyacrylate coating thickness 200 μm, microencapsulated coagulation factor spraying, curing and drying temperature 40°C.
[0116] Summarize:
[0117] This embodiment uses a nanofiber material layer combining polyethylene terephthalate and nano zinc oxide as a substrate, combined with a microencapsulated biochemical hemostatic zone and a blood stop response layer made of an expandable polymer material, to achieve a nanofiber hemostatic bandage with basic hemostatic properties. In the material design, nano zinc oxide provides basic antibacterial ability, while the electrospinning technology ensures the microporous structure of the fiber, achieving good air permeability and liquid barrier properties. This embodiment is simple in design and fully functional, and is suitable for the rapid hemostasis needs in daily trauma and common bleeding scenarios.
[0118] Example 2: Reinforced antibacterial nanofiber hemostatic bandage
[0119] Improvements:
[0120] On the basis of Example 1, the content of nano zinc oxide is increased and the fiber structure is optimized.
[0121] preparation:
[0122] Nanofiber material layer 1:
[0123] Components: polyethylene terephthalate (87 wt%), nano zinc oxide (13 wt%).
[0124] Preparation: The ultrasonic dispersion time was extended to 30 minutes, the spinning voltage was increased to 22 kV, the flow rate was 1.2 mL / h, the fiber pore size was reduced to 0.25 μm, and each square meter contained 2 g of nano zinc oxide.
[0125] Biochemical hemostasis zone 2:
[0126] Components: fibrinogen (45wt%), snake venom thrombin (15wt%), hydrophilic nanofibers (30wt%), chitosan wrapping material (10wt%).
[0127] Preparation: Chitosan was dissolved in ethanol at 20°C and the particle size of the microcapsules was controlled at 250 μm.
[0128] Blood Stop Response Layer 4:
[0129] Components: sodium polyacrylate (65wt%), microencapsulated coagulation factor (25wt%), gelatin (10wt%).
[0130] The coating thickness is 150 μm and the spraying rate is 1.5 mL / min.
[0131] Summarize:
[0132] On the basis of Example 1, the antibacterial properties of the nanofiber material layer are enhanced by increasing the proportion of nano zinc oxide and optimizing its distribution. This example further improves the precise control of the fiber pore size, reduces the possibility of bacterial invasion, and is suitable for open wounds with high infection risks or postoperative care. The design of the microencapsulated biochemical hemostatic zone and the blood stop response layer ensures efficient hemostasis in complex environments. This example is particularly suitable for postoperative care of high-risk areas for infection or contaminated wounds.
[0133] Example 3: Rapidly expanding nanofiber hemostatic bandage
[0134] Improvements:
[0135] Based on Example 2, the expandable polymer material is optimized to increase the expansion rate.
[0136] preparation:
[0137] Nanofiber material layer 1:
[0138] Components: polyvinylidene fluoride (90wt%), nano zinc oxide (10wt%).
[0139] Preparation: The spinning flow rate was adjusted to 0.8 mL / h, the fiber pore size was controlled at 0.2 μm, and the dispersion concentration of nano zinc oxide was increased to 1.8 g / m 2 .
[0140] Biochemical hemostasis zone 2:
[0141] The preparation was kept the same as in Example 2.
[0142] Blood Stop Response Layer 4:
[0143] Components: sodium polyacrylate (60wt%), microencapsulated coagulation factor (30wt%), sodium alginate (10wt%).
[0144] The coating thickness was reduced to 100 μm and the spraying speed was 1.8 mL / min.
[0145] Summarize:
[0146] Based on Example 2, this embodiment significantly improves the expansion speed and effect of the blood stop response layer by optimizing the formula of the expandable polymer material and the film layer design, making it particularly outstanding in heavy bleeding scenarios. This embodiment has the functions of rapid expansion and synergistic release of coagulation factors, forming a strong physical barrier on the wound surface and triggering an efficient coagulation mechanism, which is an ideal solution for severe bleeding scenarios such as arterial bleeding.
[0147] Example 4: Highly efficient coagulation nanofiber hemostatic bandage
[0148] Improvements:
[0149] Based on Example 3, the activity of coagulation factors in the biochemical hemostasis zone is improved.
[0150] preparation:
[0151] Biochemical hemostasis zone 2:
[0152] Components: fibrinogen (40wt%), snake venom thrombin (20wt%), hydrophilic nanofibers (30wt%), polylactic acid-glycolic acid (10wt%).
[0153] Preparation: The particle size of the emulsion was reduced to 200 μm, the concentration of the spinning solution was increased to 15 wt%, and the pore size of the fiber membrane was controlled at 0.3 μm.
[0154] Summarize:
[0155] By increasing the activity and content of the coagulation factor in the biochemical hemostasis zone, this embodiment further enhances the coagulation efficiency on the basis of embodiment 3. By adjusting the encapsulation technology of the microencapsulated coagulation factor and the liquid absorption performance of the fiber support material, the contact efficiency between the coagulation factor and the blood is improved. This embodiment is designed for large-scale surgical operations or emergency environments that require efficient and rapid coagulation, and can stop bleeding and form a stable coagulation barrier in a very short time.
[0156] Example 5: Highly durable nanofiber hemostatic bandage
[0157] Improvements:
[0158] Based on Example 4, the durability and mechanical strength of the overall material are optimized.
[0159] preparation:
[0160] Nanofiber material layer 1:
[0161] Components: polyethylene terephthalate (85wt%), polyvinylidene fluoride (5wt%), nano zinc oxide (10wt%).
[0162] Preparation: The spinning voltage is increased to 25 kV, the fiber pore size is 0.3 μm, the distribution of nano-zinc oxide is more uniform, and the content per square meter is 1.8 g.
[0163] Blood stopping response layer 4:
[0164] The coating film thickness is increased to 250 μm, and the spraying rate is 2 mL / min.
[0165] Summary:
[0166] Based on Example 4, this example focuses on optimizing the mechanical strength and durability of the overall structure. By adjusting the proportion of the base material and the coating film thickness, the service life of the bandage in complex environments is enhanced. The tear resistance of the fiber material is significantly improved, and the stability of the blood stopping response layer is also enhanced. This example is suitable for long-term wound care needs, such as postoperative hemostasis protection or battlefield first aid scenarios, ensuring the reliability and stability of long-term wearing.
[0167] Summary of summaries:
[0168] Through the gradual improvement of the above five examples, from the basic rapid hemostasis design to the enhancement of antibacterial properties, the optimization of swelling performance, the improvement of coagulation efficiency, and then to the enhancement of overall durability, it demonstrates the creative expansion of the present invention from basic functions to complex scenario applications. Through the refined design of the nanofiber material layer, biochemical hemostasis area, and blood stopping response layer, the present invention shows excellent performance in different hemostasis scenarios, fully meeting the diverse needs of daily trauma, surgical care, and emergency rescue, providing new ideas and solutions for the development of hemostasis products.
[0169] Test experiment:
[0170] I. Experimental purpose
[0171] The purpose of this experiment is to evaluate the procoagulant effect of nano-zinc oxide with different particle sizes in nanofiber hemostatic patches and hemostatic bandages and its influence on plasma coagulation time and recalcification time. Through in vitro tests and data analysis, verify the advantages of nano-zinc oxide with what nano specifications in hemostatic performance.
[0172] II. Experimental materials and sample preparation
[0173] 1. Experimental animals
[0174] Species: Male rabbits
[0175] Body weight: 2.2 ± 0.2 kg
[0176] License number: SYXK(Hebei)2017 - 005
[0177] 2. Plasma preparation
[0178] Blood collection and processing: Whole blood was collected from rabbits through carotid artery cannulation, mixed with sodium citrate anticoagulant (volume ratio 1:9), centrifuged at 3000 r / min in a refrigerated centrifuge for 15 min, platelet-poor plasma (PPP) was separated, and stored at low temperature.
[0179] 3. Sample Preparation
[0180] Sample set:
[0181] Sample 1: Contains 20nm nano zinc oxide.
[0182] Sample 2: Contains 100nm nano zinc oxide.
[0183] Sample 3: Contains 150nm nano zinc oxide.
[0184] Specifications and processing: Each sample is cut into 0.5×0.5cm 2 Set aside, or cut into pieces and weigh 20 mg for testing.
[0185] 3. Experimental Methods
[0186] 1. In vitro coagulation activity assay
[0187] Objective: To detect the effects of samples on plasma prothrombin time (PT), activated partial thromboplastin time (APTT), thrombin time (TT) and fibrinogen (FIB) levels.
[0188] Steps:
[0189] After sterilization, the samples were placed in a culture dish and incubated at 37°C for 3 minutes.
[0190] Add 100 μL of plasma, wait for it to be completely absorbed, then add 200 μL of pre-warmed PT reagent, and record the time when filaments appear as the PT value.
[0191] The APTT, TT and FIB values were determined according to the kit instructions.
[0192] Data recording: Each group was measured 3 times and the average value was taken.
[0193] The experimental results are shown in the attached diagram. Figure 5 .
[0194] 2. In vitro coagulation time determination
[0195] Objective: To determine the effect of samples on the coagulation rate of anticoagulant blood.
[0196] Steps:
[0197] 20 mg of sample was added to the test tube and incubated at 37°C for 5 minutes.
[0198] Add 1 mL of anticoagulated blood, mix well, add 500 μL of 25 mM calcium chloride solution, and continue incubation.
[0199] Tilt the test tube every 10 seconds to observe whether coagulation is formed and record the coagulation time.
[0200] The experimental results are shown in the attached diagram. Figure 6 .
[0201] 3. Determination of plasma recalcification time
[0202] Objective: To evaluate the effect of samples on the plasma recalcification and coagulation process.
[0203] Steps:
[0204] The samples were placed in 50 mL centrifuge tubes and incubated at 37°C for 3 minutes.
[0205] Add 100 μL of fresh anticoagulated blood, mix well, and then add 100 μL of 25 mM calcium chloride solution.
[0206] Observe the time when the white gel appears and record the time of recalcification.
[0207] The experimental results are shown in the attached diagram. Figure 7 .
[0208] 4. Results and Discussion
[0209] 1. In vitro coagulation activity
[0210] The experiment showed that the sample 1 (20nm nano zinc oxide) group significantly shortened the PT, APTT, and TT time, and the F IB concentration was higher than that of other groups and the blank group, indicating that it has the best procoagulant performance. As the particle size increases, the coagulation activity of samples 2 and 3 decreases, but both are better than the blank group.
[0211] 2. In vitro coagulation time
[0212] Sample 1 showed the lowest coagulation time (148.6 s), which was much better than sample 2 (166.3 s) and sample 3 (176.0 s), indicating that 20 nm nano zinc oxide had the highest efficiency in the coagulation reaction.
[0213] 3. Plasma recalcification time
[0214] The recalcification time of sample 1 was the shortest (186.7s), indicating that it was more effective in promoting the activation of coagulation factors in the recalcification reaction. The recalcification time of samples with larger particle sizes (samples 2 and 3) was slightly longer, but still significantly better than the blank group.
[0215] V. Conclusion
[0216] The experimental results verified the significant hemostatic effect of 20nm nano zinc oxide in the nanofiber hemostatic bandage, which showed the best performance in shortening coagulation time, increasing fibrinogen levels and promoting plasma recalcification. This hemostatic bandage is suitable for emergency trauma, surgical hemostasis and other rapid hemostasis needs. In contrast, although the larger particle size nano zinc oxide still has certain procoagulant properties, the effect is slightly inferior to the 20nm sample, further highlighting the effect of particle size on hemostatic performance.
[0217] Experimental design: Test on air permeability and water-tightness of fiber materials
[0218] Purpose:
[0219] The air permeability and water-tightness of the nanofiber material were verified through experiments, and its permeability to air molecules and barrier properties to liquids (including water and saline) were evaluated. At the same time, its filtering effect on bacteria was further explored to ensure its excellent protective performance as a base layer.
[0220] Experimental materials and equipment:
[0221] 1. Experimental Materials
[0222] Nanofiber samples:
[0223] Sample A: 20nm nano zinc oxide (fiber pore size 0.2μm).
[0224] Sample B: 100nm nano zinc oxide (fiber pore size 0.3μm).
[0225] Sample C: 150nm nano zinc oxide (fiber pore size 0.5μm).
[0226] liquid:
[0227] Deionized water.
[0228] 0.9% saline.
[0229] Bacterial solution:
[0230] An aqueous solution containing Escherichia coli (E. coli, about 0.5-1 μm in size).
[0231] 2. Experimental Equipment
[0232] Liquid penetration test device (fixed fiber sample for liquid dripping observation).
[0233] Air Permeability Tester.
[0234] Microbial filtration test device (bacterial filtration test).
[0235] Water column differential pressure gauge (to assess resistance to water pressure).
[0236] Constant temperature box (maintains the liquid test environment temperature at 37°C).
[0237] Experimental steps:
[0238] 1. Air permeability test
[0239] Test method:
[0240] Fix samples A, B and C on the air permeability tester.
[0241] Set the standard air pressure to 100Pa and measure the air flow rate (unit: L / m 2 / s).
[0242] Test standard:
[0243] If the air permeability is higher than 10L / m 2 / s, indicating that the material has good air permeability.
[0244] Each group of samples was tested 3 times and the average value was taken.
[0245] 2. Liquid barrier performance test
[0246] Test method:
[0247] Fix the sample on the liquid penetration test device, add 1 mL of deionized water, and observe whether the liquid penetrates to the other side of the sample.
[0248] The same procedure was repeated using 0.9% saline for testing.
[0249] Use a water column differential pressure meter to gradually increase the water pressure (unit: cmH2O) and record the critical pressure at which the sample begins to penetrate.
[0250] Test standard:
[0251] If there is no liquid penetration and the water pressure resistance value is higher than 30cmH2O, it means that the material has good impermeable performance.
[0252] 3. Bacterial filtration performance test
[0253] Test method:
[0254] Samples A, B, and C were installed in microbial filtration devices respectively.
[0255] The pressure difference (100Pa) is used to push the E. coli solution containing bacteria to flow through the sample, and the solution after passing through the sample is collected for bacterial culture counting.
[0256] Record the bacterial filtration rate (unit: %).
[0257] Test standard:
[0258] If the bacterial filtration rate is higher than 99%, it means that the sample has excellent bacterial barrier performance.
[0259] Table 1:
[0260]
[0261] Data Analysis:
[0262] Breathability:
[0263] Sample A (20nm) showed the highest air permeability (12.8L / m 2 / s), indicating that it has the best ventilation performance. The ventilation performance of samples B and C is slightly lower, but still meets the good ventilation standard.
[0264] Waterproof:
[0265] Samples A and B showed no liquid penetration, and the water pressure resistance value was higher than 30cmH2O, showing excellent water-tight performance. Sample C showed a slight amount of penetration under high pressure conditions, and its performance was slightly inferior.
[0266] Bacteria filterability:
[0267] Sample A has the highest bacterial filtration rate (99.8%), effectively blocking E. coli. The filtration rates of samples B and C are slightly lower, but both exceed 99%, meeting the high-efficiency filtration standard.
[0268] Experimental conclusion:
[0269] Through experimental verification, the nanofiber material containing 20nm nano zinc oxide (sample A) performed best in terms of air permeability, water impermeability and bacterial filtration, fully demonstrating the superiority of fiber pore size optimization and material design. The experimental results further proved that the fiber material is suitable for the application of the base layer of hemostatic bandages, and can achieve the dual functions of air permeability and protection in wound care, effectively reducing the risk of infection while maintaining a dry environment for the wound.
[0270] Working principle: Before using the nanofiber hemostatic bandage, first take it out of the package and keep it clean and hygienic. Then, gently peel off the protective sheet 5 covering the surface of the bandage to avoid direct contact between your fingers and the nanofiber material layer 1 of the bandage to prevent contamination. Align the middle part of the nanofiber hemostatic bandage, i.e., the biochemical hemostatic area 2, with the bleeding site. Make sure that the biochemical hemostatic area can directly contact the blood oozing out of the wound so that its coagulation effect can be fully exerted. Gently press the adhesive layer 3 around the bandage to make it fit firmly on the skin and ensure that the bandage is not easy to move. When the blood from the wound contacts the bandage, the biochemical hemostatic area 2 of the bandage will begin to release coagulation factors, rapidly accelerate blood coagulation, and help stop bleeding. At the same time, the blood stop response layer 4 will expand rapidly after contacting the blood, forming a physical barrier to block further bleeding, and additionally release coagulation factors to further accelerate the hemostasis process. Keep the bandage covering the wound and observe the bleeding. If the blood flow stops, the bandage can continue to remain on the wound to promote healing. During use, avoid moving the bandage frequently to avoid affecting the hemostatic effect. If the wound heals well and the bleeding has stopped, the bandage can be carefully removed. If the wound has not healed or bleeding recurs, a new hemostatic bandage can be replaced to keep the wound clean and continue hemostatic protection.
[0271] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A nanofiber hemostatic bandage, characterized in that: It includes the following structural layers, from outside to inside: A protective sheet (5), which is used to cover the surface of the hemostatic bandage before use to protect it from contamination; A nanofiber material layer (1) which serves as a base layer of the hemostatic bandage; A biochemical hemostasis zone (2) is arranged in the middle of the surface of the nanofiber material layer (1) and is used to release coagulation factors after encountering blood to accelerate blood coagulation; An adhesive layer (3) is located around the nanofiber material layer (1) and is used to fix the hemostatic bandage so that it fits on the skin; The blood stop response layer (4) is located below the biochemical hemostasis zone (2) and is used to rapidly swell to form a physical barrier and release coagulation factors after encountering blood.
2. The nanofiber hemostatic bandage according to claim 1, characterized in that: The nanofiber material layer (1) comprises components: polyethylene terephthalate, polyvinylidene fluoride substrate and 20 nm nano zinc oxide; The polyethylene terephthalate and polyvinylidene fluoride materials account for 85-95 wt % of the nanofiber material layer (1), and the nano zinc oxide accounts for 5-15 wt % of the nanofiber material layer (1).
3. The nanofiber hemostatic bandage according to claim 2, characterized in that: The preparation method of the nanofiber material layer (1) is as follows: S1.1, preparing an electrospinning solution: polyethylene terephthalate and polyvinylidene fluoride are mixed and dissolved in a mixed solvent of dimethylformamide and tetrahydrofuran at a total mass of 85-95wt%, and stirred to form a uniform solution by heating to 60-70°C; nano zinc oxide with a particle size of 20nm accounting for 5-15wt% of the solution mass is added to the solution, and ultrasonic dispersion is used for 15-20min and then continued to stir to form a uniform electrospinning solution; S1.2, electrospinning: electrospinning the electrospinning solution at a voltage of 15-25 kV, a flow rate of 0.5-1.5 mL / h, and a distance of 10-20 cm between the needle and the receiving plate, and stretching to form a nanofiber membrane with a pore size of 0.2-0.5 μm, wherein the nano zinc oxide is uniformly embedded in the fiber structure, and the content of the nano zinc oxide in each square meter of the fiber membrane is 1-2 g; S1.3, drying, heat treatment and molding: the nanofiber membrane prepared by electrospinning is left to dry at room temperature for 2-4 hours to remove the residual solvent, and then heat treated at 60-80°C for 2-4 hours, and finally cut into the required size to prepare the nanofiber material layer (1).
4. The nanofiber hemostatic bandage according to claim 1, characterized in that: The biochemical hemostatic zone (2) comprises components: biological hemostatic factors, hydrophilic nanofibers and microcapsule wrapping materials; The biological hemostatic factor accounts for 40-60wt% of the biochemical hemostatic area (2), the biological hemostatic factor is a coagulation protein and a hemostatic enzyme, the coagulation protein is fibrinogen, the hemostatic enzyme is snake venom thrombin, the hydrophilic nanofiber accounts for 20-40wt% of the biochemical hemostatic area (2), and the microcapsule encapsulation material is optionally one of gelatin, chitosan or polylactic acid-glycolic acid, which accounts for 10-20wt% of the biochemical hemostatic area (2).
5. The nanofiber hemostatic bandage according to claim 4, characterized in that: The preparation method of the biochemical hemostatic zone (2) is as follows: S2.
1. Dissolving the microcapsule encapsulation material: dissolving gelatin, chitosan or polylactic acid-glycolic acid in deionized water or ethanol at a ratio of 10-20 wt % at a dissolving temperature of 20-40° C., stirring for 30-60 min until completely dissolved to form a uniform solution; S2.2, microencapsulation of biological hemostatic factors: slowly add 40-60wt% biological hemostatic factor solution into the encapsulating material solution at a rate of 0.5-2mL / min, stir at 300-800rpm at 20-30°C to form an emulsion, and solidify the encapsulating material by evaporating the solvent or heating to obtain microencapsulated coagulation protein and hemostatic enzyme particles with a particle size of 100-500μm; S2.3, preparation of hydrophilic nanofiber support material: dissolve polyethylene glycol or polyvinyl alcohol in deionized water or ethanol at a ratio of 8-15wt%, heat to 60-70°C and stir for 1-2h to form a uniform spinning solution, and spin it into a hydrophilic nanofiber membrane by electrospinning technology at a voltage of 10-20kV, a flow rate of 0.2-1.0mL / h and a spinning distance of 10-15cm. Cut the spun nanofiber membrane into a size that meets the specifications of the biochemical hemostasis zone (2), accounting for 20-40wt% of the biochemical hemostasis zone; S2.4, microcapsule fixation: The microencapsulated biological hemostatic factor is uniformly sprayed on the surface of the hydrophilic nanofiber membrane at a concentration of 5-10wt% and a spraying rate of 0.5-2mL / min. It is naturally dried at room temperature so that the microcapsule particles are firmly attached to the surface of the hydrophilic nanofiber membrane to form a biochemical hemostatic zone (2).
6. The nanofiber hemostatic bandage according to claim 1, characterized in that: The blood stop response layer (4) comprises components: expandable polymer material, microencapsulated coagulation factor and fixed adhesive; The expandable polymer material is optionally one of sodium polyacrylate or polyurethane, which accounts for 60-80wt% of the blood stop response layer (4); the microencapsulated coagulation factors include coagulation proteins and hemostatic enzymes, which account for 15-30wt% of the blood stop response layer (4); the fixing adhesive is optionally one of sodium alginate or gelatin, which accounts for 5-10wt% of the blood stop response layer (4).
7. The nanofiber hemostatic bandage according to claim 6, characterized in that: The preparation method of the blood stop response layer (4) is as follows: S3.
1. Preparation of expandable polymer material membrane: Dissolve or disperse the expandable polymer material in deionized water at 60-80 wt% of the mass of the solution, stir evenly for 30-60 min to form an expandable solution, use a coating device to evenly coat the solution on the surface of the substrate, control the coating thickness to 100-300 μm, and dry at room temperature for 2-4 h to form an expandable polymer material film; S3.
2. Microencapsulation of biological hemostatic factors: Mix the coagulation protein and hemostatic enzyme in proportion, accounting for 40-60wt% of the mass of the biological hemostatic factor solution, add it into 40-60wt% deionized water and stir evenly, dissolve the wrapping material in deionized water or ethanol at a ratio of 10-20wt%, stir for 30-60min, and the dissolution temperature is 20-40℃; Slowly adding the biological hemostatic factor solution to the encapsulating material solution at a rate of 0.5-2 mL / min, stirring at 300-800 rpm at 20-30° C. to form an emulsion, and solidifying by volatilizing the solvent or heating to 30-50° C. to form microcapsule particles with a particle size of 100-500 μm; S3.3, Microcapsule fixation and molding: The microencapsulated biological hemostatic factor is uniformly sprayed on the surface of the expandable polymer material film at a concentration of 5-10wt% and a spraying rate of 0.5-2mL / min; S3.4, prepare the fixing adhesive solution: dissolve 5-10wt% of sodium alginate or gelatin in 90-95wt% deionized water or ethanol, heat to 40-50°C and stir evenly; S3.5, spray the fixing adhesive solution evenly on the surface of the microcapsule particles at a spraying rate of 0.5-1.5 mL / min; S3.
6. Allow the sprayed film to dry naturally at room temperature for 1-3 hours to form a blood-stopping response layer (4).
8. A nanofiber hemostatic bandage according to any one of claims 1 to 7, characterized in that: The application of the nanofiber hemostatic bandage in the following scenarios: Used for emergency trauma hemostasis, including open wounds and deep wounds; For bleeding control during surgery; Used for rapid hemostasis in battlefield emergency situations; Used for rapid hemostasis of arterial bleeding, capillary bleeding and other heavy bleeding wounds; Used for local hemostasis operation and postoperative hemostasis care in medical institutions; Used for hemostatic protection of accidental wounds in industrial or domestic environments.
Citation Information
Cited By
Degradable hemostatic bandage containing cannabidiol and preparation method
CN121154880A